Effects of the application of static magnetic fields during potato freezing. (March 2022) - Otero, Laura; Pozo, Alberto
Abstract: The effectiveness of static magnetic fields (SMFs) in improving food freezing is a topic that, nowadays, raises substantial controversy among the scientific community. To shed light on this matter, new freezing experiments, under well controlled conditions, were performed in potato samples subjected or not to SMFs of either 40–55 mT or 150–200 mT, that is, approximately 1000 and 5000 times greater than the Earth's magnetic field, respectively. Our results showed that these SMFs did not affect supercooling, freezing kinetics, or potato quality. Thus, the supercooling reached before nucleation, the duration of the precooling, phase change, and tempering steps, the characteristic and total freezing times, drip losses, texture, and color were similar in potato samples frozen with or without SMF application. More experiments, at higher SMF intensities and in foods of different composition, should be performed to definitively evaluate the effectiveness of SMFs in improving food freezing. Highlights: Potato samples were frozen subjected or not to static magnetic fields (SMFs) of either 40–55 mT or 150–200 mT. Freezing curves were compared in control and SMF experiments. SMFs produced no effect on supercooling and freezing kinetics of potato samples. SMFs did not affect drip losses, texture, or color of thawed potato.